Aerodynamic stability of cable-stayed bridges under erection - 张新军 孙炳楠 项海帆 (Journal of Zhejiang University. A. Science, 2005)
In this work, nonlinear multimode aerodynamic analysis of the Jingsha Bridge under erection over the Yangtze River is conducted, and the evolutions of structural dynamic characteristics and the aerodynamic stability with erection are numerically generated. Instead of the simplified method, nonlinear multimode aerodynamic analysis is suggested to predict the aerodynamic stability of cable-stayed bridges under erection. The analysis showed that the aerodynamic stability maximizes at the relatively early stages, and decreases as the erection proceeds. The removal of the temporary piers in side spans and linking of the main girder to the anchor piers have important influence on the dynamic characteristics and aerodynamic stability of cable-stayed bridges under erection.